Inequality and Employment in a Dual Economy : Enforcement of Labor Regulation in Brazil - Almeida, Rita; Carneiro, Pedro (World Bank, Washington, DC, 2017)
This paper studies the impact of an increase in the enforcement of labor regulations on unemployment and inequality, using city level data from Brazil. We find that stricter enforcement (affecting the payment of mandated benefits to formal workers) leads to: higher unemployment, less income inequality, a higher proportion of formal employment, and a lower formal wage premium. Our results are consistent with a model where stricter enforcement causes a contraction in labor demand in both the formal and informal sectors; and where workers value mandated benefits highly, so that there is an increase in the formal sector labor supply, an increase in the willingness to become unemployed to search for a formal sector job, and a decrease in labor supply to the informal sector.